Problems of cerebral microcirculation as a therapeutic target - D. V. Zakharov; V. A. Mikhailov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The problem of discirculatory encephalopathy(DE) - chronic cerebrovascular disease, characterized by multifocal or diffuse brain damage, and manifested a complex neurological and neuropsychological disorders. Presents information concerning the etiology and pathogenesis, morphological and clinical manifestations of the disease, diagnostic criteria and treatment guidelines vascular encephalopathy. The authors consider that modern complete diagnostics of discirculatory encephalopathy allows to implement an adequate tactics of treatment, to choose a complex therapy effective for all spectrum of pathogenetic and clinical variants of the disease as well as to provide prophylactics of DE complications. Timely treatment improves not only the patient’s quality of life but considerably prolongs the period of his active social activity.